Trends in Online Religious Processes during the Coronavirus Pandemic in Hungary—Digital Media Use and Generational Differences - Mónika, Andok (Religions, 2021)
The present study shows how Hungarian churches and religious communities responded to the physical closure and relocation to online spaces in the spring of 2020, since while physical gates became closed, digital gates became opened. In the churches, work began in two directions with particular intensity. On the one hand, they organized their online appearance. On the other hand, they began to rethink their theological reflections on the possibilities of digital technology. The study also analyses both the event- and community-based presence of the churches as well as what they broadcast to their believers. The intention was to find the answer to what the presence of the camera meant in the process of live broadcasting, with a special focus on the visual elements and procedures that differed from the visual perception of real presence during streaming: the camera movement, the different viewing angles, the location of the cameras, the cut, and the sound quality. In other words, the believers had a new visual experience, an optical representation of reality, which afforded them a new type of interactivity and participation. In addition, the study highlights the generational differences that can be explored in digital transitions.